Digital Storytelling sebagai Pra-Pengalaman: Bagaimana Narasi Digital Membentuk Niat Kunjungan dalam Pariwisata Heritage - Catharina Aprilia Hellyani; Mar'atul Fahimah; Agni Malagina (MARGIN ECO, 2026)
Tourism marketing has increasingly shifted from attribute-based perspectives toward experience- and meaning-oriented approaches, particularly in heritage tourism. However, limited empirical attention has been given to how tourism experiences are pre-constructed through digital narratives at the pre-visit stage. This study examines how digital storytelling operates as a pre-experience mechanism shaping visit intention in heritage tourism, by integrating perspectives of tourism experience, motivation, destination knowledge, and attitude toward destination. Adopting an interpretive qualitative approach, the study was conducted in Lasem, a community-based heritage city in Rembang Regency, Central Java, Indonesia. Data were collected through group deep interviews involving five informants comprising heritage practitioners and community actors in Lasem, and were analyzed using thematic analysis. The findings reveal that visit intention is shaped by the alignment between digital narratives and lived heritage experiences, which subsequently influences tourists' attitudes and intentions to visit or recommend the destination. Theoretically, this study extends understanding of tourism experience construction at the pre-visit stage. Practically, the findings offer strategic implications for destination managers to develop authentic digital storytelling that aligns with actual on-site experiences in community-based heritage destinations.